2005
DOI: 10.1515/jpm.2005.054
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and prematurity – where do we stand?

Abstract: Erythropoietin (EPO) treatment for anemia of prematurity is still controversial. Large multicentric trials demonstrate that administration of EPO+Fe cannot prevent early transfusions, particularly in very low birth weight newborns and in infants with severe neonatal diseases, but may have some beneficial effect to prevent late transfusions. Current treatment of anemia of prematurity should be multifactorial trying to minimize all causes that reduce erthrocytic mass (phlebotomies, use of noninvasive procedures)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 64 publications
0
13
0
1
Order By: Relevance
“…1,2 However, the fundamental clinical objective of using rEPO in very low birth weight (VLBW) infants has been to slow down the decline in hemoglobin parameters during the first weeks of life and to reduce the transfusion requirement, which is very high for these infants. [3][4][5][6][7] Since the first pilot trial, published by Halperin et al in 1990, 8 rEPO use has spread and many studies have evaluated it as safe and effective. [9][10][11][12] In terms of efficacy, rEPO stimulates erythropoiesis in VLBW infants and diminishes the number of transfusions per infant as well as the cumulative volume transfused and the exposure to multiple donors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 However, the fundamental clinical objective of using rEPO in very low birth weight (VLBW) infants has been to slow down the decline in hemoglobin parameters during the first weeks of life and to reduce the transfusion requirement, which is very high for these infants. [3][4][5][6][7] Since the first pilot trial, published by Halperin et al in 1990, 8 rEPO use has spread and many studies have evaluated it as safe and effective. [9][10][11][12] In terms of efficacy, rEPO stimulates erythropoiesis in VLBW infants and diminishes the number of transfusions per infant as well as the cumulative volume transfused and the exposure to multiple donors.…”
Section: Introductionmentioning
confidence: 99%
“…Control of phlebotomies and the use of strict transfusion criteria by themselves lower the transfusion requirement. 6,7 Regarding safety, long-term adverse effects are still unknown, 6 but in the short term, rEPO does not increase neonatal morbidity (sepsis, necrotizing enterocolitis, intraventricular hemorrhage, chronic lung disease, death before discharge, hypertension). [10][11][12] Nevertheless, because of its demonstrated angiogenic activity, 13 several trials have associated the use of rEPO with retinopathy of prematurity (ROP).…”
Section: Introductionmentioning
confidence: 99%
“…However, others reported that the effect of EPO treatment was insufficient in reducing RBC transfusions to be of clinical significance in the treatment of anemia of prematurity (5,25,38). These differences may be due to inconsistent transfusion guidelines, treatment protocols, and/or interpatient variability in EPO responsiveness (9). Also, since none of the study designs considered the complex pharmacokinetics/pharmacodynamic (PK/PD) of EPO, this likely resulted in empirical EPO doses and dosing schedules that were suboptimal.…”
mentioning
confidence: 99%
“…Combined treatment with erythropoietin, oral iron substitution, vitamin B12 and folic acid [18,19] starting in the first week of life can decrease the need for transfusion in preterm infants [8,42].…”
Section: C+mentioning
confidence: 99%